Measurements of Turbulent Fluxes of Momentum and Sensible Heat over the Labrador Sea - Bumke, Karl; Karger, Uwe; Uhlig, Klaus (AMS (American Meteorological Society), 2002)
Turbulent fluxes of momentum and sensible heat were estimated from sonic anemometer measurements gathered over the Labrador Sea during a winter cruise of the R/V Knorr. The inertial dissipation method was used to calculate turbulent fluxes of momentum. The resulting drag coefficients agree well with earlier findings. Sensible heat fluxes were computed using both cross-correlation and inertial dissipation techniques. There is good agreement between results from both methods, although there is more scatter in the correlation fluxes than the dissipation fluxes. The inertial dissipation method gives reasonable results even under conditions of high wind speeds and low air temperatures, which combined with the relatively warm sea surface temperatures lead to sensible heat fluxes of several hundred watts per square meter. Sensible heat fluxes obtained from the sonic anemometer measurements agree well with bulk turbulent fluxes according to the formulation of Isemer and Hasse.